KOMPETENSI PROFESIONAL DAN PEDAGOGIK GURU DALAM PEMBELAJARAN KRIYA KERAMIK DI SMK NEGERI 8 PADANG - Rahmat Alisyah Putra, Drs. Suib Awrus, M.Pd., Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study was to describe the teacher's professional competence and pedagogical competence of ceramics craft teachers at SMK Negeri 8 Padang. This type of research is descriptive research with qualitative research methods. Professional competency is the mastery and proficiency of ceramics learning materials in a broad and in-depth manner that enables guiding students to meet the competency standards set out in the National Education Standards (SNP).Keywords: Competence, Professional, Pedagogic